Nursing of a patient with post-stroke constipation treated with moxibustion combined with auricular acupoint pressing based on the brain-gut axis theory (基于脑-肠轴理论艾灸联合耳穴压豆干预1例脑卒中后便秘患者的护理体会) - ZHANG Ping (张平); LIU Hua (刘华); YANG Xing (杨星) (中西医结合护理)
This paper summarized the nursing management of constipation in a stroke patient. Based on the brain-gut axis theory, the moxibustion combined with auricular acupoint pressing therapy and individualized nursing interventions were carried out to relieve the abdominal distension and anxiety of the patient. Based on the interaction of the brain-gut axis theory, nursing by syndrome differentiation is conductive to relieve the constipation and improve the recovery of gastrointestinal function in patients with post-stroke constipation. (本文回顾1例脑卒中后便秘患者的临床资料, 总结护理经验。基于脑-肠轴理论实施艾灸及耳穴压豆治疗, 同时配合健康宣教等个体化护理措施, 患者便秘伴随症状腹胀、焦虑都得到改善。基于脑-肠轴理论大脑与胃肠相互影响、相互调节思想对患者进行辨证施护, 解决患者便秘及焦虑症状, 有利于患者胃肠功能的恢复。)